Levinas and the Night of Being : a Guide to Totality and Infinity. - Moati, Raoul (Fordham University Press, 2016)
A close reading of Emmanuel Levinas's masterpiece Totality and Infinity which leads to a rehabilitation of the Metaphysical question beyond its deconstructive critique during the XXth Century.